Comparison of frequency and morphological characteristics of variations of gravity and magnetotelluric fields - Yu. V. Antonov; A. K. Rybin; V. E. Matiukov (Известия высших учебных заведений: Геология и разведка, 2015)
The joint change variations of magnetotelluric field of the Earth and un-tidal variations of gravity, registered on the territory of Bishkek Geodynamic Polygon, are considered. There is a clear relationship of these variations. Obviously, a joint analysis of the variations of magnetotelluric field and gravity gives a new possibility to study the deep structure and dynamics of geo-medium.